2016
DOI: 10.18632/oncotarget.14214
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment models to evaluate the necessity of prostate biopsies in North Chinese patients with 4-50 ng/mL PSA

Abstract: BackgroundProstate-specific antigen (PSA) is widely used for prostate cancer screening, but low specificity results in high false positive rates of prostate biopsies.ObjectiveTo develop new risk assessment models to overcome the diagnostic limitation of PSA and reduce unnecessary prostate biopsies in North Chinese patients with 4–50 ng/mL PSA.MethodsA total of 702 patients in seven hospitals with 4–10 and 10–50 ng/mL PSA, respectively, who had undergone transrectal ultrasound-guided prostate biopsies, were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Interestingly, TBCD could strike a balance with diagnostic efficiency, showing a sensitivity of 79.31% and specificity of 81.58% in the validation set. A Chinese cohort study showed that prostate biopsy had lower positive diagnostic rates at PSA levels of <50 ng/ml [23]. Thus, we further evaluated the diagnostic ability in three PSA range subgroups, 4-10, 4-20, and 4-50 ng/ml, and showed that the sensitivity and specificity were both higher than 80%.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, TBCD could strike a balance with diagnostic efficiency, showing a sensitivity of 79.31% and specificity of 81.58% in the validation set. A Chinese cohort study showed that prostate biopsy had lower positive diagnostic rates at PSA levels of <50 ng/ml [23]. Thus, we further evaluated the diagnostic ability in three PSA range subgroups, 4-10, 4-20, and 4-50 ng/ml, and showed that the sensitivity and specificity were both higher than 80%.…”
Section: Discussionmentioning
confidence: 93%
“…The most commonly used marker in the diagnosis of prostate cancer is PSA [2]. The upper limit for gray-zone PSA has been determined as 10 ng/ml in numerous studies [6][7][8]15,[17][18]. Some other studies, though few in number, suggest that the upper limit for gray-zone PSA may show ethnic variation and propose that this limit is likely to be higher in countries where PCa is less common, particularly in Far Eastern countries [9,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies, though few in number, suggest that the upper limit for gray-zone PSA may show ethnic variation and propose that this limit is likely to be higher in countries where PCa is less common, particularly in Far Eastern countries [9,19]. Zhao et al [6] determined the gray-zone PSA range as 4-10 ng/ml. Based on this range, the authors detected PCa in 17% of the patients that underwent SPB and in 50% of the patients with a gray-zone PSA level of 10-50 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation